Perioperative Cardioprotection by Remote Ischemic Conditioning - Cho, Youn Joung (Int J Mol Sci, 2019)
Remote ischemic conditioning has been investigated for cardioprotection to attenuate myocardial ischemia/reperfusion injury. In this review, we provide a comprehensive overview of the current knowledge of the signal transduction pathways of remote ischemic conditioning according to three stages: Remote stimulus from source organ; protective signal transfer through neuronal and humoral factors; and target organ response, including myocardial response and coronary vascular response. The neuronal and humoral factors interact on three levels, including stimulus, systemic, and target levels. Subsequently, we reviewed the clinical studies evaluating the cardioprotective effect of remote ischemic conditioning. While clinical studies of percutaneous coronary intervention showed relatively consistent protective effects, the majority of multicenter studies of cardiac surgery reported neutral results although there have been several promising initial trials. Failure to translate the protective effects of remote ischemic conditioning into cardiac surgery may be due to the multifactorial etiology of myocardial injury, potential confounding factors of patient age, comorbidities including diabetes, concomitant medications, and the coadministered cardioprotective general anesthetic agents. Given the complexity of signal transfer pathways and confounding factors, further studies should evaluate the multitarget strategies with optimal measures of composite outcomes.